Influence of ICT Access and Utilization on Academic Performance of Science Students in Selected Private Secondary Schools in Ibadan - Gbotosho, Ajibola Sunmade (MiddleBelt Journal of Library and Information Science, 2020)
This study investigated the influence of ICTs access and utilisation on academic performance of science students in selected private secondary schools in Ibadan. Alongside four specific objectives, two research questions and two hypotheses were formulated. The research design employed is the descriptive survey design. Data were collected from 156 science students from six private secondary schools in Ibadan with the use of questionnaire. The data analysis was done with the use of Descriptive statistics such as frequency and percentage distribution and Pearson’s correlation. Findings revealed the ICT facilities that were made available to include that: the science students had access to television at school, home and cyber café. Hence, the average performance of the students in science subjects was 60-64%, and that ICTs access (r=.148**, N=156, P<0.05) and ICTs utilisation (r=.254**, N=156 and P<0.05) has significant positive relationship with academic performance of the students. There is significant joint influence of ICT access and utilisation on academic performance of the science students (R=.282 and a multiple R2 of .079) and F-ratio of 6.595 (p<0.05). The main challenge was that students could not have access to most of the ICT facilities at schools. Therefore, the study recommended that both teachers and students should update their ICT skills, ICT newest editions should be provided by government, non-governmental organisations and proprietors, recruitment of technology personnel as ICT facilitators, among others.